A Case of Thyroid Storm Induced by Iodine-Containing Dietary Supplements and Homeopathic Remedies. (June 2014) - Karkowski, Katie; Carroll, James L.
Objective : We report the case of a patient who presented to the hospital in thyroid storm following the use of several iodine-containing dietary supplements (DS) and homeopathic remedies (HR).Case Summary : The patient was a 76-year-old woman with no personal or family history of thyroid or autoimmune disease. On laboratory assessment, a thyroid panel showed that her total T3 and T4 were elevated at 334 ng/dL and 14.6 µg/dL, respectively; thyroid stimulating hormone was undetectable; and thyroid stimulating immunoglobulin was positive at 7.4. The patient had been consuming 170 µg of iodine daily for the past 2 months via her DS and HR. An objective causality assessment using the Naranjo adverse drug reaction probability scale revealed that an adverse effect was probable. The patient likely suffered from iodine-induced thyrotoxicosis secondary to the consumption of numerous DS and HR.Discussion : Dietary supplements and homeopathic remedies can pose significant health risks. The safety of these products is not assured as they are incompletely monitored by the Food and Drug Administration. Individuals who take these compounds do so at their own risk and should pay close attention to product contents.Conclusions : The labeling of DS and HR products may be misleading. Pharmacists and clinicians are advised to inquire about the use of DS and HR products. When use is identified, the products should be subject to a thorough review.